Categorisation of Foot Complaints in Systemic Lupus Erythematosus (SLE) From a New Zealand Cohort - Otter, S; Rohan, M; Davies, K; Kumar, S; Gow, P; Dalbeth, N; Corkhill, M; Panthakalem, S; Rome, K (BioMed Central, 2017)
Background: Foot complaints have been shown to be common in systemic lupus erythematosus (SLE) and heterogeneous in nature. We aimed to categorize self-reported foot complaints in people with SLE and foot symptoms. Methods: A self-administered validated questionnaire was posted to 406 people with SLE attending adult rheumatology clinics across three health boards in Auckland, New Zealand. In addition to foot pain, vascular complaints, dermatological lesions and neurological symptoms were included in the analysis. Pairwise correlations among the variables were undertaken followed by factor analysis to identify and categorise associations between reported foot complaints. Results: From the questionnaires returned, 93 full datasets were analysed. Participants’ were predominantly female (n = 87, 93.7%), with mean (SD) age of 50.4 (14.3) years and a mean (SD) disease duration of 13.1 (11) years. Three categories of foot complaint were determined: ‘foot pain’, ‘skin disorders’ and ‘vascular insufficiency’. These three groups provided the best fit (0.91) to describe the wide range of foot complaints reported by those with SLE. Factor analysis for foot pain demonstrated a high positive loading for the inter-correlation of foot pain in past month (0.83), foot pain today (0.71), intermittent claudication (0.71), numbness (0.62), loss of balance (0.81), swelling (0.59), foot joint pain (0.77), arch pain (0.68) and tendon pain (0.77). Skin disorders demonstrated a very high positive loading for 3 factors skin rash (0.82), blistering skin rash (0.95) and foot ulceration (0.88). In vascular insufficiency a high positive loading for cold feet (0.83), chilblains (0.76) and Raynaud’s phenomenon (0.70). Conclusions: This work suggests people with SLE report three independent categories of foot complaints; foot pain, skin disorders or vascular insufficiency.
Keywords: Systemic lupus Erythematosus; Foot complaints; Foot pain; Vascular; Dermal